Examining the Role of Marine Mammals and Seabirds in Southeast Alaska’s Marine Ecosystem Dynamics - Rhodes-Reese, Melissa; Clay, David; Cunningham, Curry; Moriles-Miller, Janet; Reese, Cheryl; Roman, Joe; Warren, Joseph D.; Pearson, Heidi C. (Frontiers in Marine Science, 2021)
Primary producers are the foundation of marine food webs and require reliable nutrient sources to maintain their important role with ecosystems. While marine mammals and seabirds can play critical roles in marine nutrient cycling, their contributions are often overlooked. Southeast Alaska’s marine environment supports abundant marine mammal and seabird populations in addition to valuable fisheries. Nonetheless, there is still relatively little known about nutrient sources and fluxes in this region which is a critical component of fisheries management. The goal of our study was to advance knowledge of the role of mammals and seabirds in marine nutrient cycling and to understand how changing marine mammal and seabird populations may alter ecosystem dynamics. We utilized qualitative network models (QNMs) to examine how a simulated Southeast Alaska ecosystem would respond to an increase in marine mammals, seabirds, and nutrients. Researchers are increasingly utilizing QNMs as a first step in the development of ecosystem-based fisheries management plans as their adaptable nature is well suited to address rapidly changing climatic conditions. Our results indicate that marine mammals and seabirds make important contributions to marine nutrient concentrations in the region and that these valuable ecosystem services should not be overlooked.